Farmers’ Perception about Major Insect Pests of Cucurbits and Their Management - Tripathi, Subina; Shah, Kabita Kumari; Tiwari, Injila; Shrestha, Jiban (Talenta Publisher, 2020)
A survey was undertaken in five Village Development Committees (VDCs) of Lamjung District, Nepal from June to August 2018 to investigate major insect pests and their management practices in cucurbits. A total of ninety-five cucurbit growers were selected and interviewed using semi-structured questionnaires. The study revealed that the major insect pests attacking cucurbits were fruit fly, red pumpkin beetle, aphid, whitefly, epilachna beetle, cucurbit sting bug, cutworm, and blister beetle. The majority of farmers responded that fruit fly was the most prevalent insect pest, followed by aphid and red pumpkin beetle. Most of the farmers used chemical methods, that includes biological, mechanical, and cultural techniques to control the insects. For the mechanical method, they used sex-pheromone traps i.e. cue-lure. Among botanical pesticides, Neem (Azadirachta indica), Malabar Nut (Justicia adhatoda), Chinaberry (Melia azedarch), Mugwort (ArtemisiaÂ spp.) were used. Commonly used insecticides by farmers were Cypermethrin, Dimethoate, Malathion, and Endosulfan. The indiscriminate use of chemical pesticides resulted in pest resistance, resurgence, and sometimes outbreak of insect pests. Majority of farmers were using chemical methods to control pests. Apart from this, Integrated Pest Management (IPM) was also adopted for good agricultural practices (GAP) to prevent chemical hazards on human health and the environment. To control insect pests, trained farmers should be encouraged to follow the sanitation of fields and protection of natural enemies by avoiding the use of pesticides a long as possible.